STRUCTURE AND DYNAMICS OF SOME TROPOPHILOUS FORESTS IN WEST AFRICA (IVORY COAST) - (:unkn) unknown (My University, 1984)
This work contributes to the knowledge of the dry and semi-deciduous forests of Ivory Coast, but is also linked to the more general problems of the savannah-forest transition. It was conducted through the study of two sites; the Sudanian savannah in the north of the country, has a tropical climate with two seasons, the Guinean preforest savannah in the center of the country, has a four season tropical climate. The climatic conditions and the soil moisture regimes of the two sites are depicted. Structure and dynamics of the savannah-forest transition were analysed with respect to both the savannah-forest mosaic and the forest edge. The change of savannah into forest was the most often observed evolution in the V-Baoulé. Processes of forest-edges dynamics were analysed. The analysis of forest successions based upon the ordination of ‘floristic-structural” groups. Structural changes along successions were assessed in semi deciduous and dry forests. The specific structures of communities of various successional stages were analysed. Species richness, Shannon diversity index and equitability were calculated. In addition species abundance distributions were examined in relation to four models: Mac-Arthur broken-stick, Motomura, Preston log-normal and Pareto. Significant variations of the indices and of the models' parameters according to forest types were revealed. Successions were also characterised by temporal sequential variations of models' parameters. Processes of colonisation and maturation in Lamto semi-deciduous forests were thus described and compared to those of rain forests and dry forests. Growth and production of communities were also assessed. The radial growth of the trees and the variability of the basal area according to communities' maturity and climatic conditions were analyzed. In addition, the interindividual variability of growth rhy
Keywords: African Research